Experimental Study Comparative Compressive Strength and Tensile Strength of Nail Fiber Concrete Against Fiber Concrete - Wiraningrum, Widya; Baehaki, Baehaki; Darwis, Zulmahdi (Jurnal Fondasi, 2023)
Concrete has high compressive strength but weak tensile strength. The innovations to increase tensile strength is addition fiber. Fiber concrete has been proven increase the tensile strength, but the basic material from flammable plastic and difficult to find in Indonesia, making polypropylene fibers less desirable, so an innovation was to add nails to concrete mix as substitute for polypropylene fibers. Nails made of steel, non-flammable, higher melting point than polypropylene, high tensile strength and easy to find in Indonesia. The purpose of this study was to determine the effect of adding nail and polypropylene fiber to the compressive and split tensile strength of concrete, and to determine the optimum proportion of nail fiber to polypropylene fiber concrete. Mix design using SNI 7656:2012. Based on the results, the compressive strength of normal concrete was 20,007 MPa and 1% polypropylene concrete was 20,097 MPa. The compressive strength of nail fiber concrete varies 0,5%, 1%, 1,5%, 2% and 2,5%, respectively, 16,334 MPa, 18,790 MPa, 21,290 MPa, 21,324 MPa, 19,242 MPa. The split tensile strength of normal concrete is 1,834 MPa and 1% polypropylene concrete is 2,361 MPa. The split tensile strength of nail fiber concrete varies 0,5%, 1%, 1,5%, 2% and 2,5%, respectively, 1,620 MPa, 1,990 MPa, 1,942 MPa, 1,800 MPa, and 1,730 MPa. The optimum proportion of nail fiber concrete as substitute for 1% polypropylene fiber concrete is variation of 1,5% with compressive strength of 21,290 MPa and split tensile strength of 1,942 MPa.